Management of thyroid disorders during and after pregnancy - М. С. Черенько; С. М. Черенько (Publishing House TRILIST, 2019)
The state of the art review of the recent recommendations of American Thyroid Association and Endocrine Society comprehensively elucidates the most important issues of management of pregnant women with thyroid disorders. Authors shown that not only pregnancy impact thyroid function and course of thyroid diseases, but also functional thyroid changes can seriously affect mother and fetus. Thyroid stimulating hormone levels are significantly reduced by 0.1-0.4 mIU/ml for the lower limit of norm and by 1.0 mIU/ml for the upper in I trimester of pregnancy under the influence of placental chorionic gonadotropin, the. Total thyroxine and triiodothyronine increase significantly from the first weeks of pregnancy by 1.5 times the upper limit due to the significant increase in thyroxine binding globulins. Free triiodothyronine and thyroxine decreases in the second half of pregnancy and during labor is an average of 10-15% lower. Positive antibodies to thyroperoxidase and thyroglobulin are determined often in pregnancy. International clinical standards are not recommended to carry out a total screening of thyroid hormones in the first trimester of pregnancy. Thyroid-stimulating hormone evaluation is need only in risk groups with thyroid gland pathology. In Ukraine evaluation of this hormone may be recommended for every pregnant woman in the first trimester or at the time of the first visit. Hypothyroidism occurs in about 0.5% of pregnant women, and its main cause is autoimmune thyroiditis. The drug of choice for the hypothyroidism treatment is levothyroxine. Other drugs have no grounds for use. The most common cause of autoimmune hyperthyroidism is diffuse toxic goiter, which occurs in 0.1-1% of all pregnancies, and first place belong to gestational hyperthyroidism among non-autoimmune causes (1-3%). Subclinical hyperthyroidism of any origin does not require treatment during the entire pregnancy. Treatment with selenium is not recommended by any clinical guidelines, even in women with positive anti-thyroid antibodies. Benign thyroid nodes do not require treatment during pregnancy, and in cases of differentiated cancers, moderate suppressive therapy with thyroxine drugs can be used.